Testing budget sustainability in Sarawak state - Teo, Hui Fern (Universiti Malaysia Sarawak, (UNIMAS), 2010)
This study examines sustainability of the budget stance of Sarawak state during the period of 1970-2008. Using the usual intertemporal borrowing constraint as a framework, the study tests the long run relationship between government revenue and expenditure.